DOP84 IBD-related hospitalization and surgery rates in biologic-naïve patients with IBD treated with vedolizumab versus other biologics: Results from a long-term, prospective, observational study. (30th January 2023) - Sebastian, S; Siegel, C; Siegmund, B; Zhou, J; Jones, S; Adsul, S; Louis, E
Abstract: Background: Hospitalisations and surgeries are a major driver of health resource utilisation increasing disease burden on patients (pts) with ulcerative colitis (UC) and Crohn's disease (CD). This analysis aimed to evaluate the number of hospitalisations and surgeries among pts with UC and CD initiating vedolizumab (VDZ) or other biologic treatment, as a marker for disease modification and health resource utilisation. Methods: Secondary outcome data from a multicentre, observational, prospective, cohort post-authorisation safety study (PASS; NCT02674308) of biologic-naïve pts with UC or CD initiating VDZ or other biologic treatment were utilised. Pts received treatment under routine standard of care with clinical decisions at the discretion of treating physicians, and so treatment could be modified or changed without the need to withdraw from the study. Inflammatory bowel disease (IBD)-related hospitalisation rate and occurrences of IBD-related surgeries were assessed in pts initiating VDZ and other biologic. Time to first hospitalisation and surgery was also assessed. Results: In total, 1149 pts with UC (556 initiating VDZ, 593 initiating other biologics) and 1338 pts with CD (312 initiating VDZ, 1026 other biologics) were included in this analysis. Baseline characteristics are displayed in Table 1. VDZ-treated pts with UC had fewer IBD-related hospitalisations (12.9% vs 25.0%; risk ratio [RR] 0.52 [95% CI 0.40, 0.67]) and IBD-related surgeries (4.3% vs 10.1%; RR 0.43 [0.27, 0.68]) than those treated with other biologics (Table 2). With regard to surgical procedures, VDZ-treated pts with UC had fewer total colectomies (RR 0.40 [0.20, 0.80]), colectomy (RR 0.32 [0.13, 0.79]) and other IBD-related surgeries (RR 0.37 [0.17, 0.78]). Among pts with CD, those treated with VDZ had fewer IBD-related hospitalisations (19.2% vs 26.4%; RR 0.73 [0.57, 0.93]) and IBD-related surgeries (7.1% vs 13.8%; RR 0.51 [0.33, 0.78]) than those treated with other biologics (Table 2). Pts with UC treated with VDZ had a longer time to event of first IBD-related hospitalisation and primary and secondary IBD-related surgery (in pts without history of IBD-related surgery at baseline) than pts treated with other biologics (Table 3). Conclusion: In this large multinational, observational study, fewer biologic-naïve pts with UC or CD on VDZ treatment had hospitalisations and IBD-related surgeries than pts on other biologics. These real-world data suggest VDZ as a first line biologic treatment may contribute to modifying the course of IBD over time. Further research into the role of additional factors associated with differences in biologic treatments shown here is warranted.